2012
DOI: 10.1002/chin.201217013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structure Resolution of RbLaF4.

Abstract: Synthesis and Structure Resolution of RbLaF 4 . -RbLaF 4 is synthesized by solid state reaction of a 1:1 mixture of LaF3 and RbF (Ar, 425°C, 2 d). The compound is characterized by powder X-ray and neutron diffraction, 87 Rb, 139 La, and 19 F MAS NMR spectroscopy, DFT calculations, and electrical conductivity measurements. RbLaF4 crystallizes in the orthorhombic space group Pnma with Z = 4. The structure contains alternating LaF 9 and RbF 7 polyhedra layers. RbLaF 4 exhibits a low ionic conductivity from room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The geometry of the cylindrical TEPC reflects a simplified geometry of the real detector employed in this study and it is the same reported in (Rollet 2010) that referred to the Italian National Institute for Nuclear Physics mini-TEPC that was prototypal to the one described in (Conte et al 2019). The sensitive volume of the new mini-TEPC is structured in the same way from the point of view of simulations since the gas ducts are not implemented in the geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry of the cylindrical TEPC reflects a simplified geometry of the real detector employed in this study and it is the same reported in (Rollet 2010) that referred to the Italian National Institute for Nuclear Physics mini-TEPC that was prototypal to the one described in (Conte et al 2019). The sensitive volume of the new mini-TEPC is structured in the same way from the point of view of simulations since the gas ducts are not implemented in the geometry.…”
Section: Methodsmentioning
confidence: 99%
“…The optimization of a MC tool to interpret experimental microdosimetric spectra can be useful for testing new detectors or new experimental set ups. Previous studies have also been done with this aim in different radiation fields, with different detectors and different MC codes (Rollet et al 2010, Bohlen et al 2012, Chiriotti et al 2014, Chiriotti et al 2017, Galer et al 2017. In this paper, the microdosimetric extension of TOPAS (Perl et al 2012, Zhu et al 2019 was used to simulate the response of a mini-TEPC that measured in the 62 MeV mono-energetic proton beam of the clinical CATANA facility at the Southern National Laboratories (LNS) of INFN (Cirrone et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To identify analogs for each entry in the MPDB, we utilized the Mcule database (11) and extracted a set of compounds in SMILES format, which we downloaded. We then calculated Tanimoto coefficients or similarity scores using the OpenBabel software (12).…”
Section: Analogs Collectionmentioning
confidence: 99%